Effects of manual therapy techniques in the treatment of pain in post mastectomy patients: systematic review - Basilio, Franciane Batista; Anjos, Raphaela de Medeiros Miranda dos; Medeiros, Elany Pereira de; Melo, Elaine Marques Franco de; Silva, Rodrigo Marcel Valentim da (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Cancer is now the third leading cause of death in the world, surpassed only by cardiovascular accidents and deaths by external causes, among them stands mammary carcinoma. Mastectomy is in a procedure consisting of invasive breast removal due to some anatomical and functional changes previously diagnosed. With the growth of the disease and its high content in increasingly young women, Manual Therapy has been used as a new form of treatment. Objective: To show the effects of manual therapy in patients after mastectomy surgery. Method: This is a systematic review in which secondary and tertiary sources were used, and the databases PubMed, Medline, Lilacs and SciELO were used. It was adopted as inclusion criteria studies classified as: a randomized controlled trial, with publication period between 2009 and 2013. Were used as search terms: “Mastectomy”, “Neck”, “Shoulder Pain”, “Musculoskeletal Manipulations” and “Functionality”. Results: Among the 37 initially selected by electronic search in the databases of articles, 25 were excluded for the title did not meet the inclusion criteria. Of the 12 retained studies, 5 were excluded for duplicity. Seven studies were selected for a more thorough analysis through summary, 2 of them being excluded. The remaining 5 articles were evaluated from reading the text. It can be seen that the manual therapy techniques have significant results in the alleviation of muscle pain in patients submitted to surgery mastectomia. Conclusion: It can be seen that the manual therapy techniques have significant results in the alleviation of muscle pain in patients undergoing the mastectomy surgery. However, there is still a lack of studies of type randomized controlled trial on the effects of manual therapy in patients in the postoperative period of mastectomy